THE ROLE OF MUSLIMS IN SOCIAL LIFE OF AMERICA IN THE 20TH CENTURY (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
This article offers an in-depth analysis of the contributions and impact of Muslims on the social life of America during the 20th century. It delves into the multifaceted roles undertaken by Muslim individuals and communities, spanning areas such as civil activism, religious expression, community development, and the interplay between faith and identity within the American context. Through historical analysis and cultural insights, the article aims to provide a comprehensive understanding of the diverse ways in which Muslims have shaped and influenced American social life.